Theologians and Their Bellies: The Erasmian Epithet Theologaster during the Reformation. - Ptaszyński, Maciej (Erasmus Studies (2451-9723), 2021)
An analysis of the role and meaning of the epithet "theologaster," coined by Erasmus of Rotterdam in his letter from Paris in 1497, can reward us with insights into the interplay of Reformation, scholastic, and humanist forces in the sixteenth century. Although Erasmus rarely used the term in his later correspondence or in his works, the epithet gained some popularity among the humanists and the reformers. During the confessional debates, both sides, the Catholics and the Protestants in the Holy Roman Empire and in France, reached for this same epithet as an argument and a weapon with which to demonstrate the incompetence of their opponents. The term, however, can rarely be found in the confessional polemics in Poland, despite the enormous popularity of Erasmus in the region. The history of the epithet sheds light on the importance of the humanist legacy for the confessional era.